FLUVIAL GEOMORPHOLOGY-BASED STRATEGIES FOR ENHANCING STREAM RESTORATION AND FLOOD MANAGEMENT IN THE YAMUNA RIVER BASIN - S S Mense (Universal Research Reports, 2018)
The Yamuna River, a major tributary of the Ganges in northern India, plays a vital role in the region's hydrology, ecology, and economy. However, over the past few decades, the river has been significantly altered due to human activities such as urbanization, industrialization, and agricultural practices. These changes have led to a degradation of the river's natural geomorphological characteristics, resulting in increased flooding, loss of biodiversity, and impaired water quality. This paper explores the application of fluvial geomorphology principles to enhance stream restoration and flood management in the Yamuna River Basin. By understanding the geomorphological processes that shape river channels, sediment transport, and floodplain dynamics, more sustainable and effective management strategies can be developed. The study reviews the geomorphological characteristics of the Yamuna River Basin, the impacts of human activities on these characteristics, and proposes restoration and flood management strategies grounded in fluvial geomorphology. Case studies from the Yamuna Basin and other international river restoration projects are discussed to illustrate best practices and potential challenges. The paper concludes with recommendations for integrating geomorphology-based strategies into broader watershed management plans, considering socio-economic and political constraints, and the role of technological innovations in sustainable river management.